Serum Level of the Angiotensin-Converting Enzyme in Patients with Idiopathic Acute Optic Neuritis: A Case-Control Study - Heshmatollah Ghanbari; Alireza Dehghani; Awat Feizi; Arman Amirkhani; Mohsen Pourazizi (Scientifica)
Purpose. To evaluate the serum level of angiotensin-converting enzyme (ACE) as an important component of the renin-angiotensin system (RAS) in optic neuritis (ON) compared to the healthy control group in the context investigating the possible role of ACE in ON pathogenesis. Methods. This case-control study was conducted on patients with ON and healthy controls. Serum ACE levels were assessed and compared between the two groups by using commercially available kits by ELISA for ACE. Results. Sixty-five ON patients (75.4% female, mean age 29.70 ± 8.30 years) and 65 controls (75.4% female, mean age 29.66 ± 8.36 years) were enrolled. The median serum ACE levels were 33.5 U/L (range: 25–540) and 26 U/L (range: 22.3–72) for the ON patients and controls, respectively. Serum ACE levels were significantly higher in the patients than in the control group (P<0.001). High level of serum ACE (defined as a serum ACE >65 U/L) was present in 9 (13.8%) patients with ON and 2 (3.1%) controls. Conclusion. Our results indicated that the serum level of ACE appeared to be significantly higher in acute ON than in normal controls.